2013
DOI: 10.2478/s13382-013-0152-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between a biomarker of exposure to polycyclic aromatic hydrocarbons and semen quality

Abstract: Objectives: Growing evidence supports the reproductive and developmental toxicity of polycyclic aromatic hydrocarbons (PAHs) from prenatal and postnatal exposure, but the results of epidemiological studies regarding harmful effects of PAHs exposure on male reproductive system still remain limited and inconclusive. The aim of the present study was to investigate the relationship between 1-hydroxypyrene, a biomarker of polycyclic aromatic hydrocarbons exposure and semen quality. Materials and Methods:The study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…Thirteen studies examine the association between main semen parameters and environmental outdoor air pollution [1729]. Three studies were performed in USA [1820], five in China [21, 22, 2729] and two in Poland [23, 24] and in Czech Republic [17, 26] and one in Italy [25]. In six of the presented studies the study population was recruited from general population [17, 19, 21, 22, 25, 26].…”
Section: Summary Of Collected Datamentioning
confidence: 99%
See 3 more Smart Citations
“…Thirteen studies examine the association between main semen parameters and environmental outdoor air pollution [1729]. Three studies were performed in USA [1820], five in China [21, 22, 2729] and two in Poland [23, 24] and in Czech Republic [17, 26] and one in Italy [25]. In six of the presented studies the study population was recruited from general population [17, 19, 21, 22, 25, 26].…”
Section: Summary Of Collected Datamentioning
confidence: 99%
“…In six of the presented studies the study population was recruited from general population [17, 19, 21, 22, 25, 26]. The level of PAHs were analyzed in four studies [22, 24, 28, 29] in urine [24, 28, 29] and blood [22].…”
Section: Summary Of Collected Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have been conducted on the impact of environmental chemical exposure on the male reproductive system. Several of these studies have shown significant associations with endocrine disruptors such as polycyclic aromatic hydrocarbons and phthalates, and decreases in testosterone levels and semen quality [ 3 , 4 , 5 , 6 ]. In humans, long-term exposure to endocrine-disrupting chemicals has been shown to have harmful effects on reproductive health by interfering with the development and function of sex hormones [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%